2016
DOI: 10.1073/pnas.1525602113
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan adversity and later adulthood telomere length in the nationally representative US Health and Retirement Study

Abstract: Stress over the lifespan is thought to promote accelerated aging and early disease. Telomere length is a marker of cell aging that appears to be one mediator of this relationship. Telomere length is associated with early adversity and with chronic stressors in adulthood in many studies. Although cumulative lifespan adversity should have bigger impacts than single events, it is also possible that adversity in childhood has larger effects on later life health than adult stressors, as suggested by models of biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
115
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 75 publications
6
115
2
Order By: Relevance
“…36,37 It has been demonstrated that adverse life events at a young age increase the odds of short telomeres; in contrast, comparable experiences in adults have not demonstrated a similar biologic impact. 38 The current study has several limitations. First, temporal changes in the survivors' clinical or biochemical parameters could not be assessed, because only crosssectional data were available.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…36,37 It has been demonstrated that adverse life events at a young age increase the odds of short telomeres; in contrast, comparable experiences in adults have not demonstrated a similar biologic impact. 38 The current study has several limitations. First, temporal changes in the survivors' clinical or biochemical parameters could not be assessed, because only crosssectional data were available.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, social, traumatic, and psychological experiences associated with having cancer in childhood may become embedded epigenetically and lead to long‐term, or even permanent, alterations in gene expression . It has been demonstrated that adverse life events at a young age increase the odds of short telomeres; in contrast, comparable experiences in adults have not demonstrated a similar biologic impact …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significant amounts of telomere shortening were explained by decreased telomerase activity in the cells that express this enzyme, suggesting that measuring telomerase activity in human cells may be informative (Lin et al, ). Several reports indicate that short telomeres may be associated with central obesity (García‐Calzón et al, ; Mundstock et al, ), lifetime accumulation of stress (Epel et al, ; Osler, Bendix, Rask, & Rod, ; Puterman et al, ), increased risk of cardiovascular events (Baragetti et al, ; Hammadah et al, ), reduced immune response to influenza vaccination (Najarro et al, ), mortality (Batsis et al, ; Goglin et al, ; Heidinger et al, ), and several adverse health outcomes (Lin et al, ; Lorenzi et al, ; Lustig et al, ; Sanders & Newman, ). Genetic mutations associated with short telomeres have been shown to cause dyskeratosis congenita, pulmonary fibrosis, and several other severe medical conditions that are grouped under the definition of “telomere syndrome” (El‐Chemaly et al, ; Ungar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on the relation between childhood SSS and telomere length is inconsistent. While several recent studies are supportive of the association (Cohen et al, ; Puterman et al, ), an early meta‐analysis found no relation (see, Robertson et al, ). Developing a better understanding of the conditions under which childhood SSS is associated with telomere length is important given that telomere length is an indicator of cellular aging.…”
Section: Introductionmentioning
confidence: 97%
“…The evidence on the relation between childhood SSS and telomere length is inconsistent. While several recent studies are supportive of the association (Cohen et al, 2013;Puterman et al, 2016), an early meta-analysis found no relation (see, Robertson et al, 2013).…”
mentioning
confidence: 99%